ANALISIS ARUS KAS UNTUK MENILAI KINERJA KEUANGAN PADA PT KERETA API INDONESIA (Persero) - Heni Risnawati; Hasna Mudiarti; Tuti Nadhifah (Universitas Wahid Hasyim, 2023)
The purpose of this studi to analyze the financial performance of PT Kereta Api Indonesia (Persero) in 2019- 2021 using a cash flow measurement tool. The ratios used in this study are five ratios including the ratio of operating cash flows to current liabilities, the ratio of operating cash flows to interest, the ratio of operating cash flows to capital expenditures, the ratio of operating cash flows to total debt and the ratio of operating cash flows to net income. The research method uses secondary data, namely the financial statements of PT KAI (Persero) for 2019-2021. The sampling technique uses a purposive sampling method where samples are taken with a specific purpose. The sample in this study is the financial statements that have been audited for three years. The results show that the ratio of operating cash flow to interest, the ratio of operating cash flow to capital expenditure has a fairly good performance. As for the ratio of operating cash flow to current liabilities, operating cash flow to total debt and the ratio of operating cash flow to net income, the performance was not good.Keywords : cash and cash equivalents, cash flows, financial reports, financial performance